Mumps-specific antibody persistence in children aged 3-7 years immunized with two doses of mumps-containing vaccines: A prospective cohort study in Jiangsu Province, China - Jinfang Sun; Mingma Li; Lei Zhang; Xiuying Deng; Ying Hu; Qiang Chen; Zhiguo Wang; Xiang Sun; Yuanbao Liu (Taylor & Francis Group, 2023)
Mumps reemergence has been reported in developed countries with high levels of two-dose mumps-containing vaccine (MuCV) coverage. The effectiveness of the two-dose MuCV may be compromised by limitations in the persistence of immunity. This prospective cohort study evaluated the persistence of immunity of a two-dose MuCV in children aged 3-7 years from 2015 to 2020. Persistence of antibody to mumps, determined as the geometric mean antibody concentration (GMC), and seropositivity were analyzed for both repeated measurements from three follow-ups and on each cross-section, respectively. A total of 105 eligible subjects were recruited. Their overall seropositivity rate was relatively high and stable (92.4%-84.8%), while the overall GMC decreased from 547.6 U/ml to 333.3 U/ml. Analysis of waning immunity in 91 participants showed a significant and consistent downward trend for GMC, which differed significantly in boys and girls. The overall seropositivity rate decreased slightly from 2015 (95.6%) to 2016 (92.3%) but both were significantly higher than in 2018 (84.6%). The rates in girls remained stable, while those in boys declined to 75% in 2018. The seropositivity rate of the cross-section level decreased from 95.4% to 86.4% in 4 years. Although two-dose MuCV may result in a high level of immunity, antibody concentrations decay over 2 years after the second dose. Children with waning immunity after receiving two doses, especially boys, require further surveillance at 4 years and later to avoid future mumps epidemics. Clinical trial registration: NCT02901990.